Aplikasi Penyaluran Sampah Anorganik Non-Residu berbasis Android - Daniel Christian Tedja; Alexander Setiawan; Lily Puspa Dewi (Jurnal Infra, 2020)
Environmental pollution is increasing every day along with the increasing number of products and consumption behavior of the society in general. Things that must be done to overcome the increase in the volume of waste are to reduce the production of waste, especially inorganic types because it is very difficult to decompose and increasing society awareness to dispose of waste. Viewed from these two aspects, society need a system that is able to give them encouragement to dispose of wasteThe Android-based non-residual inorganic waste distribution application intended to help the owner in raising public awareness to dispose of waste, especially non-residual inorganic type. This application will be made using the Java programming language using Android Studio. This android-based application helps the admin to add as many drop post as possible so that it can reach the people in the city of Surabaya evenly. In addition, this application also records the submission process that has been confirmed by the confirmator also picked up waste by the courier so that the admin get the waste collected data.The test results show that this application runs well on devices with Android 7.1.1 (Nougat) but does not run well for Android 4.4.3 (KitKat) because some features can only run on Android 7.0.0 (Nougat) and above. This application runs the waste submission feature, the addition of the drop post, the notification feature, displays submission information, chat feature, and the navigation feature that makes it easy for the society to use the application so that it is expected to encourage the society to dispose of their inorganic waste.